INDUSTRIAL APPLICATIONS OF FILTER AIDS - Vasudeo Zambare (Engineering Heritage Journal)
Filter aids is a salicaceous inert material for separation of liquid and particulate matters. In general filter aids are obtained from mining where diatomaceous earth and perlite are dominantly used as filter aids for industrial applications. The filter aid has important properties of its rigidness, chemically inertness, insoluble, porous, high permeability, and remove finest particles at high rate. Due to its good stability, less impurities, it is on high demand for separation of high purity products of food, beverages and pharmaceutical industries.